Bibliometric analysis of adverse drug reactions and pharmacovigilance research activities in Nepal - Sunil Shrestha; Krisha Danekhu; Bhuvan KC; Subish Palaian; Mohamed Izham Mohamed Ibrahim (SAGE Publishing, 2020)
Background: Bibliometric analyses have been used previously to study the measures of quality and impact of research performed in several health-related areas such as adverse drug reactions (ADRs) and pharmacovigilance (PV), etc. This method can assess the research performance of publications quantitatively and statistically. There is no evidence of bibilometric studies analyzing ADRs and PV from Nepal. Therefore, the present study aimed to assess scientific output on ADRs and PV-related research activities in Nepal using a bibliometric analysis of publications from 2004 January to December 2018, that is, 15 years. Methods: A systematic search was conducted in PubMed, Web of Science, Google Scholar, Scopus and Nepal Journal Online (NepJOL) databases. 'Adverse Drug Reactions' or 'ADRs' or 'ADR' or 'Adverse drug reaction' or 'AE' or 'Adverse Event' or 'Drug-Induced Reaction' or 'Pharmacovigilance' or 'PV' and 'Nepal'. The search covered 15 years (January 2004 to December 2018) of study on ADRs and PV in Nepal. Only articles retrieved from databases were included, whereas published/unpublished drug bulletins, pharmacy newsletters and thesis were excluded. The articles thus retrieved were recorded, and thereafter analyzed. Word count code was used for the analysis of keywords used in the retrieved articles. Results: A total of 124 articles were retrieved, with the highest rate of publications in 2006 and 2007, with 16 papers each. Among the articles, 10 (8.1%) were published in Kathmandu University Medical Journal (KUMJ). Single papers were published in 38 different journals. Brief reports (1.6%), case reports (31.2%), case series (0.8%), education forums (0.8%), letters to the editor (5.6%), original research articles (41.9%), review articles (9.7%), short communications and short reports (8.1%) on ADRs and PV were recorded. Out of 124 papers, 52 (41.9%) were original research publications. The majority (74.1%) of research was done in the category of ADR incidence, types, prevention, and management, followed by policy and suggestions for strengthening national and regional pharmacovigilance centers of Nepal (14.5%). Conclusions: During the study years, there was an increase in scientific publications on drug safety. A total of 124 published articles were found during bibliometric analysis of ADRs and PV research activities in Nepal.